(untitled) (International Journal of Physiotherapy, 2016)
Background: Recently increasing concern among stress is seen during health care undergraduate students but there is lack of such studies in physical therapy students in Pakistan. Higher stress levels the students in their education the effect of stress in physical therapy students throughout is well documented in western countries. This study aims at assessing the level of perceived stress among physical therapy students of Isra University. Method: It’s a Cross-sectional type of descriptive study that was conducted on hundred physical therapy students of Isra institute of rehabilitation sciences, ISRA University, Hyderabad. A Convenient, non-probability technique of sampling is used. All the Physical therapy students were included. Results: Overall response rate was 100%. Moderate level of stress was found in 73% students (scored between 51-75%), severe level of stress was found in 8% students (scored >75%) whereas low level of stress was found in 19% of students (scored between 25-50%). Conclusion: The current study presents the level of stress perceived by physical therapy students of Isra University, Hyderabad. The findings of the study revealed higher levels of stress in the physical therapy students. Majority of student perceived moderate stress and about 8% of students reported severe stress. Further detailed and generalized studies are needed to evaluate the causes, effects and coping approaches adapted by the students. Furthermore level of stress should also be correlated with academic performance of the students. Findings of such studies may help to initiate certain strategies that may help students overcome their stress and cope efficiently with the upcoming problems.